Lipophilic compounds and thermal behaviour of African mango (Irvingia gabonensis (Aubry‐Lecomte ex. O'Rorke) Baill.) kernel fat. (5th September 2018) - Lieb, Veronika M.; Schuster, Laura K.; Schmarr, Hans‐Georg; Carle, Reinhold; Steingass, Christof B.
Summary: Irvingia gabonensis kernels are a promising oleiferous source. Their total lipid content was 72.3%. C14:0 and C12:0 represented the most abundant fatty acids. Triacylglycerols with ECN 32 and 46–48 were identified for the first time by HPLC‐DAD‐ESI‐MS n . Comprehensive GC‐FID and GC‐MS analyses revealed novel insights into minor lipids like phytosterols and tocochromanols. Among the latter, γ‐tocopherol was found to be the major vitamer. β‐Sitosterol and stigmasterol were the prevailing phytosterols in the kernel fat. The high saturation level of the fat resulted in a sharp differential scanning calorimetry melting curve with a high melting temperature of 42.1 °C. The fat remained solid over a wide temperature range and still contained 66.6% solid fats at 35 °C. Consequently, kernels of the African mango provide a viable source for the recovery of solid fats applicable in the food industry as sustainable alternatives to replace palm‐based fats or hardened vegetable oils. Abstract : Characterisation of lipophilic compounds and thermal behaviour of Irvingia gabonensis kernel fat applicable in the food industry as a sustainable alternative for palm‐based fats or hardened vegetable oils.